2014
DOI: 10.1002/jat.2971
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of brain regions reflecting aberrations in nervous system development targeting the process of neurite extension of rat offspring exposed developmentally to glycidol

Abstract: We previously found that exposure to glycidol at 1000 ppm in drinking water caused axonopathy in maternal rats and aberrations in late-stage hippocampal neurogenesis, targeting the process of neurite extension in offspring. To identify the profile of developmental neurotoxicity of glycidol, pregnant Sprague-Dawley rats were given drinking water containing glycidol from gestational day 6 until weaning on day 21 after delivery, and offspring at 0, 300 and 1000 ppm were subjected to region-specific global gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…In a 28‐day study neurotoxicity developed in 5‐week‐old Sprague‐Dawley rats which were given glycidol by gavage at 0, 30 or 200 mg/kg bw per day (Akane et al., ). Neurotoxicity was only observed at highest dose in which rats showed progressively increasing abnormalities of the gait along with essentially the same lesions of central and peripheral nervous systems as those also observed in pregnant rats (Akane et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…In a 28‐day study neurotoxicity developed in 5‐week‐old Sprague‐Dawley rats which were given glycidol by gavage at 0, 30 or 200 mg/kg bw per day (Akane et al., ). Neurotoxicity was only observed at highest dose in which rats showed progressively increasing abnormalities of the gait along with essentially the same lesions of central and peripheral nervous systems as those also observed in pregnant rats (Akane et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…CNTN3 belongs to the Ig superfamily of proteins and its function is primarily associated with the properties of this family. Akane et al (23), illustrated that the rat ortholog of CNTN3, Cntn3 , functions in neurite outgrowth-promotion, and when treated with glycidol at 1,000 ppm, axonopathy occurred and the expression of CNTN3 was altered. Morales et al (10), found an isolated cryptic proximal interstitial 3p deletion, del(3) (p12.3p13) in a patient with neurodevelopmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…Neural circuits can be assessed by measuring neurite growth, synaptogenesis, and myelination (Brat and Brimijoin 1992). Glycidol exposure increases the gene expression of Kl, Igf2, and Igfbp2 in the corpus callosum to promote myelination, while Efnb3, Tnc, and Cd44 gene expression increases in the cingulate cortex promote neurite growth (Akane et al 2014). The safety of galactose (Powell et al 1986) and methylmercury (Parran et al 2003) has been assessed by measuring neurite growth.…”
Section: Neural Circuit-based Toxicity Assaysmentioning
confidence: 99%